Investigating the small lung: which imaging procedure?. Issue 9 (September 1982) - Gordon, I; Helms, P
Abstract : Ventilation and perfusion radionuclide lung scans, using krypton 81m and technetium-99m macroaggregates, were performed together with a variety of other imaging procedures in 18 children aged between 1 week and 13 years in whom radiology had shown a small lung. Radionuclide scans provided an assessment of regional ventilation and perfusion unobtainable by other means, and 4 main categories of disturbed function could be seen in the radiological small lung–namely, absence of ventilation and perfusion, absent perfusion with preserved ventilation, generalised or segmental decreases in ventilation, and perfusion and segmental perfusion defects in areas of decreased ventilation. The clinical history and other imaging procedures, including fluoroscopy and penetrated mediastinal views, enabled a firm diagnosis to be made in each of these 18 patients. In 3 main pulmonary arteries were absent, 2 had lung aplasia, 2 had lobar aplasia, 9 had varying degrees of pulmonary hypoplasia (two with additional sequestrated segments), 1 had lobar emphysema, and 1 had post-infective lung mal-development (MacLeod's syndrome).